Technology Adoption in Local Governance: Moderating Effects of Readiness for Change on Digital Leadership and Information Technology Capability - Anedi, Achmad Edwyn; Suparto Wijoyo; Setijaningrum, Erna (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study investigates the adoption of digital technology in Indonesian village governance, specifically through the "Desaku Pintar" program aimed at digitizing Population Data Administration. It addresses the existing challenges of low public adoption rates and declining satisfaction indicators, aiming to explore how Digital Leadership and Information Technology Capability influence technology acceptance and usage within the public sector, and the moderating role of Readiness for Change. Utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, this study employed a quantitative survey method involving 270 village government staff members. Data were analyzed through Structural Equation Modeling (SEM) using the AMOS software to test the proposed relationships and moderating effects. The study finds that Digital Leadership and IT Capability have a significant positive impact on Acceptance and Use of Technology. Specifically, Digital Leadership (β=0.724, p<0.001) and IT Capability (β=0.200, p=0.025) substantially enhance technology acceptance when moderated by Readiness for Change. The moderating effect of Readiness for Change was also confirmed, strengthening the relationship between Digital Leadership (β=0.116, p=0.041) and IT Capability (β=0.132, p=0.035) on technology acceptance. This research makes a novel contribution by integrating Readiness for Change into the UTAUT framework, contextualized within Indonesian village governance. Practically, the findings offer valuable insights for policymakers to enhance digital leadership and IT capabilities, facilitating effective technology adoption and improved public service delivery. Future research should employ longitudinal designs, mixed methods, and multilevel analyses, incorporating theories like Diffusion of Innovation (DOI) for deeper insights.